The impact of internal trade liberalizations on plant productivity and markups - Daniel Teeter (Queen's University, Department of Economics, 2024)
I estimate the effects of two Canadian internal trade liberalizations on plant-level productivity, markups, and exports. In particular, I examine the New West Partnership and Trade Agreement (NWPTA) and the Trade and Cooperation Agreement (TCA), both of which sought to reduce or remove prohibitive, technical and administrative barriers to trade across provinces. Employing a control function approach, I use Canadian manufacturing data to estimate plant-level total factor productivity and markups for 2004-2012. Then, using difference-in-differences methods, I find that the NWPTA increased the likelihood that a plant exports interprovincially, increased the share of output that plants sell to other provinces, increased plant-level total factor productivity but had no significant impact on plant-level markups. The agreement raised the average plant's productivity by 1.97 percent across all post-treatment years. In contrast, the TCA had no significant impact on plant-level productivity or export behavior, but was associated with a a small increase in markups. The NWPTA has shown significant positive effects on plant performance compared to the TCA, which has significant implications for the design of internal trade agreements. Specifically, the NWPTA's negative-list approach, in contrast to the TCA's positive-list, resulted in broader coverage. Moreover, the NWPTA achieved greater progress in mutually recognizing worker certifications and business registration, as well as in harmonizing business standards between provinces, making it a more effective agreement overall.
Keywords: F13; F14; L11; L38; 330; Inter-regional trade barriers; Trade agreements; Productivity; Markups; Canada